2015
DOI: 10.1002/ppul.23255
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity after elective resection of prenatally diagnosed asymptomatic congenital pulmonary airway malformations

Abstract: Resection of prenatally diagnosed asymptomatic CPAM is associated with a significant risk of complications, which may be life threatening. These data contribute to a balanced discussion of risks and benefits for these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Elective surgery is not without risk and postoperative complications occurred in 5% of asymptomatic infants, including air leak, infection, effusion and death in one case 11. Hall et al 44 45 recently reported a complication rate of 23% in a case series of 60 patients with asymptomatic CPAM who underwent surgery. This included complications in three cases defined as major: tension pneumothorax, aggressive chest wall fibromatosis and near fatal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Elective surgery is not without risk and postoperative complications occurred in 5% of asymptomatic infants, including air leak, infection, effusion and death in one case 11. Hall et al 44 45 recently reported a complication rate of 23% in a case series of 60 patients with asymptomatic CPAM who underwent surgery. This included complications in three cases defined as major: tension pneumothorax, aggressive chest wall fibromatosis and near fatal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of these children are now diagnosed prenatally and therefore have clinically relevant data that must be extracted from the maternal medical record prior to analysis [12]. Delivering evidence-based, quality care with complication rates that are as low as possible is especially critical for asymptomatic CLMs given that we, as pediatric surgeons, are asking families to consent to a major operation performed relatively infrequently for an incidentally identified lesion that may or may not cause any problems later in life [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Reports of thoracosopic lobectomy for CLM vary and some have described high conversion rates (up to 20%) and significant complications. [6][7][8] The only previous meta-analysis of thoracoscopic and open CLM resection included 216 patients from six reports (all pre-2010), two of which described only four patients in each treatment arm. [9][10][11] Since this report, there has been a large number of highvolume case series of CLM resection.…”
Section: Introductionmentioning
confidence: 99%